Pemberdayaan Warga Benteng Sorawolio melalui Pembuatan Kain Tenun Khas Buton Kota Baubau - Iin Septianingsih; Marwan Kurniawan; Vista Rahmadani; Siti Sarah; Muslimin Muslimin (Pusat Riset dan Inovasi Nasional, 2024)
Buton's traditional woven cloth is a local cultural heritage with economic, social, and cultural value for the people of Baubau City. However, with the advancement of modernization, the younger generation's interest in continuing the weaving tradition has waned. This has resulted in a decline in the number of weavers and limited the development of local culture-based businesses. This community service activity aims to improve community skills in making Buton's traditional woven cloth, encourage community economic empowerment, and preserve local culture by strengthening traditional weaving businesses. The activity implemented a participatory approach through field observation, outreach, woven cloth production training, production assistance, and product marketing. The target group included housewives, small business owners, and the younger generation in Baubau City. The results showed an increase in participants' knowledge and skills in the process of making Buton's traditional woven cloth, from material selection and dyeing techniques to the weaving process. Furthermore, this activity also increased community motivation to develop weaving businesses as a source of family income and expanded marketing opportunities for products based on local culture. This empowerment program is expected to support the development of the community's creative economy while maintaining the sustainability of Buton's traditional woven cloth heritage in Baubau City.